2020
DOI: 10.1108/ijph-09-2019-0052
|View full text |Cite
|
Sign up to set email alerts
|

The priority health issues and key health determinants of detained Filipino children

Abstract: Purpose Rising societal pressures for the Filipino urban poor population – precipitating increased crime – alongside widespread corruption, have led to many children being both lawfully and unlawfully detained in child rehabilitation centres. Far from rehabilitating, detained children live in prisonlike conditions, despite the illegality of child imprisonment in the country. Their human rights disregarded; they suffer from abuse, neglect and a multitude of health issues, with no access to healthcare. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Additionally, studies have shown that overcrowding in prisons is a key factor influencing the well-being and mental health of young prisoners (MacDonald, 2018). A qualitative study among detained Filipino adolescents found that mental health was one of the commonly reported eight key health issues, while food, overcrowding and hygiene were mentioned as the main determinants of their health (Blount, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, studies have shown that overcrowding in prisons is a key factor influencing the well-being and mental health of young prisoners (MacDonald, 2018). A qualitative study among detained Filipino adolescents found that mental health was one of the commonly reported eight key health issues, while food, overcrowding and hygiene were mentioned as the main determinants of their health (Blount, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Более высокая распространенность психических расстройств среди несовершеннолетних осужденных в сравнении со сверстниками подтверждается многочисленными зарубежными исследованиями [2][3][4]. Немаловажным фактором нарушения психического здоровья в научных исследованиях показана так называемая социальная депривация [5,6], а также факторы изоляции, отвержения в пенитенциарных учреждениях [7][8][9][10].…”
unclassified